SUPERVISI AKADEMIK KEPALA PONPES DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN ISLAM DI PONPES IBNU ABBAS BOJONEGORO - Bramasta, Rangga; Iskandar Zulkarnain; Ita Evina (UNISAN JURNAL, 2025)
This study aims to describe the form of academic supervision carried out by the principal of the Ibnu Abbas Islamic Boarding School in Bojonegoro and how this supervision influences the improvement of the performance of Islamic Education teachers. Educational supervision plays a very important role in the Islamic education system because it functions to improve the quality of educators, the effectiveness of the learning process, and student learning outcomes. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of educational supervision in Islamic boarding schools does not only focus on improving academic competence, but also on spiritual development, morality, and exemplary behavior of both teachers and students. Supervision is carried out with the principles of deliberation, guidance, and exemplary behavior that refer to Islamic values. The main challenges faced by teachers include limited supporting facilities, differences in ability to understand concepts and the application of authentic assessment, and a lack of focus on students in the final stages of development. Overall, this study concludes that Islamic-based supervision has the potential to shape professional, innovative, and noble educators in creating an integrated learning process between intellectual and spiritual aspects. It shows that academic supervision is implemented through planning, classroom observation, ongoing training, and structured evaluation. The implementation of academic supervision has been proven to be able to improve pedagogical competence, professionalism, and teacher work responsibilities.